Peran Koperasi Sekolah dalam Menumbuhkan Jiwa Wirausahawan pada Diri Siswa - Suparmi, Ni Wayan; Suwena, Kadek Rai; Meitriana, Made Ary (Universitas Pendidikan Ganesha, 2020)
The purpose of this study was to determine the role of school cooperatives in fostering entrepreneurial spirit among students at Vocational High School Number 1 Gianyar. This type of research was descriptive research, the data collection instruments was using questionnaires and documentation. The populations in this study were students in marketing major at Vocational High School Number 1 Gianyar with the amount of 208 students with a total sample of 137 people using random sampling techniques. This research used descriptive analysis to analyze data. The results of data analysis showed that the role of school cooperatives in terms of the dimensions of forming good and independent rescue practices was in the category of very strong roles, in terms of the dimensions helping in realizing an atmosphere of direct training to practice techniques management and trade techniques in the category of very strong roles, in terms of having the characteristics and elements of democracy among the younger generation in the category very strong role, in terms of the dimensions of promoting cooperation attitude and mutual assistance to help each other were in the category of very strong role, and in terms of the dimension of growing leadership talent among the younger generation scores 4,109 with the percentage score of 85.6% was very strong category.